Lingkungan Kerja dan Kepuasan Kerja Karyawan Bagian Produksi di Industri CPO - Elsa Febriani; Syamsul Anwar (UIN Sultan Syarif Kasim Riau, 2015)
A work environment is place where employees perform their daily work activities. Job satisfaction is one important indicator of improving labor productivity. Need to know whether the work environment influence on employee job satisfaction. This study aimed to determined effect of work environment both physical and non-physical to employees satisfaction. The study conducted on employees in a palm oil mill. There were 43 employees of production departement became object of the research. Data collected through observation, interview, and questionnaires. The method of analysis using multiple regression analysis by testing simultaneous effect (F-test) and testing partial effect (t-test).The test results indicatedthat the questionnaires were reliable and valid. Results of multiple regression analysis indicated that the work physical and non-physical environment significantly affected employee satisfaction either simultaneously or partially.Some aspects of the work environment that need attention and improvement by the management of the palm oil mill were also given.Key words: employees satisfaction, palm oil mill, work environment,